PENGGUNAAN ECO-BRICK SEBAGAI MEDIA PEMBELAJARAN ANAK PRASEKOLAH DI PAUD KENDEDES - Andini Kusuma; Susi Herawati; Sarwiti Sarwiti; Siti Kholifah (LPPM Universitas Bina Bangsa, 2023)
The aim of this activity is to increase the knowledge and skills of Kendedes PAUD Serang City teachers in using ecobricks as a learning resource, especially as a starting material for making educational toys (APE). Ecobricks are ecological materials that do not decompose, obtained from used plastic bottles. This activity was motivated by the many waste problems, namely: (1) There is still a large amount of plastic waste in the environment that has not been utilized optimally, (2) Lack of knowledge regarding handling and disposal of plastic waste. . free environmentally friendly materials. teaching tools, (3) The nature of love for the environment in children will not develop without stimulation from the teacher. Based on this background, activities focus on teacher training to utilize eco-boards as a learning environment using environmentally friendly APE. The training method is carried out through lectures, questions and answers, demonstrations and practice in preparing APE. The results obtained indicate a growth in teachers' knowledge and skills in disposing of plastic waste using eco-bricks as a tool. Teachers can share their experiences with children and their parents